Impact of Digital Marketing Tools on Consumer Behavior in Nepal - Sharma, Surya Prasad; Paudel, Shishir (Journal of Rapti Babai Campus, 2025)
This research investigates the impact of digital marketing on e-commerce businesses in Nepal, focusing on how digital marketing tools influence consumer behavior and business performance. As internet usage grows, businesses increasingly use strategies like social media, email marketing, and search engine optimisation to engage consumers and enhance online sales. Data were collected from 246 respondents across Nepal using the convenience sampling method through structured questionnaires and analyzed using a descriptive research design. The findings indicate that digital marketing plays a significant role in increasing the frequency of online purchases and improving customer satisfaction. Consumers who interact with digital advertisements, particularly through social media and search engines, report greater satisfaction and are more likely to engage in repeat purchases. Additionally, access to detailed product information and reviews enhances the appeal of e-commerce platforms. Despite these positive effects, challenges such as mistrust in online payment systems and a preference for traditional in-person shopping still limit the broader adoption of e-commerce in Nepal. The study concludes that while digital marketing effectively drives engagement and sales, businesses must address these barriers to realize the full potential of the e-commerce market. Personalized digital marketing strategies and efforts to build trust in online platforms are recommended.